Mixing in large-scale vessels stirred with multiple radial or radial and axial up-pumping impellers: modelling and measurements - Vrabel, P; van der Lans, R; Luyben, K; Boon, L; Nienow, A (Elsevier, 2000)
Mixing phenomena are regarded as one of the major factors responsible for the failure to successfully scale up some bioprocesses. Such phenomena have been investigated within the framework of an EC project `Bioprocess Scale-up Strategy'. Mixing in bioreactors depends on energy input, impeller type, reactor configuration and impeller geometry. Here, two different reactors of volumes 12 and 30 m3 were used, and they were equipped with either multiple Rushton turbines or with a combination of a Scaba 6SRGT radial impeller with multiple 3SHP axial up-pumping hydrofoils above it. Mixing time, power consumption, gas hold-up and liquid velocities were measured at different stirrer speeds and aeration rates in water. At the same total specific power input, aeration did not influence the mixing time much unless it changed the bulk flow pattern. A considerable reduction of mixing time was achieved if the upper impellers were axial instead of radial Rushtons at the same power consumption. The improvement with the axial impellers could be related to the reduction of axial flow barriers due to different circulation flow patterns. The Compartment Model Approach (CMA) was used to develop a flow model based on the general knowledge of the hydrodynamics of both unaerated and aerated stirred vessels. The model was successfully verified for different impeller and reactor configurations and different scales with measured pulse response curves, using either a fluorescent or a hot water tracer. The model can be used for process design purposes.